2012
DOI: 10.1111/j.1752-0118.2012.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Retail Therapy: The Enjoyment of the Consumer

Abstract: The discourse of economics and consumerism has not only penetrated into the clinical setting; it has had a pervasive effect upon each of us and upon the society in which we live. This state of affairs is taken up by reference to the now commonly used phrase 'retail therapy', in order to examine the implications of the promotion of this concept. These ideas are further elaborated through an examination of the consumerist bent our societies have taken, promoting as they do an unfettered enjoyment of consumer goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…PED does not only need to be essentially attractive; it also provides emotional worth to consumers and gives them an opportunity to enjoy and improve EWB (El Hedhli et al , 2013). Furthermore, some researchers (Atalay and Meloy, 2011; Plastow, 2012; Irwin, 2018) have suggested that retail stores can be used as a constructive idea with a strategic approach to intensify positive emotions, as these provide emotional relief and help consumers to reduce stress and negative emotions.…”
Section: Effect Of Antecedentsmentioning
confidence: 99%
“…PED does not only need to be essentially attractive; it also provides emotional worth to consumers and gives them an opportunity to enjoy and improve EWB (El Hedhli et al , 2013). Furthermore, some researchers (Atalay and Meloy, 2011; Plastow, 2012; Irwin, 2018) have suggested that retail stores can be used as a constructive idea with a strategic approach to intensify positive emotions, as these provide emotional relief and help consumers to reduce stress and negative emotions.…”
Section: Effect Of Antecedentsmentioning
confidence: 99%